Comparison of Munsell® color chart assessments with primary schoolchildren's self-reported skin color - Wright, C. Y.; Reeder, A. I.; Gray, A. R.; Hammond, V. A. (Skin research and technology, 2015)
Background Skin color is related to human health outcomes, including the risks of skin cancer and vitamin D insufficiency. Self‐perceptions of skin color may influence health behaviours, including the adoption of practices protective against harmful solar ultraviolet radiation levels. Misperception of personal risk may have negative health implications. The aim of this study is to determine whether Munsell® color chart assessments align with child self‐reported skin color. Methods Two‐trained investigators, with assessed color acuity, visually classified student inner upper arm constitutive skin color. The Munsell® classifications obtained were converted to Individual Typology Angle (ITA) values and respective Del Bino skin color categories after spectrocolorimeter measurements based on published values/data. As part of a written questionnaire on sun protection knowledge, attitudes, and behaviours, self‐completed in class time, students classified their end of winter skin color. Student self‐reports were compared with the ITA‐based Del Bino classifications. A total of 477 New Zealand primary students attending 27 randomly selected schools from five geographic regions. The main measures were self‐reported skin color and visually observed skin color. Results A monotonic association was observed between the distribution of spectrophotometer ITA scores obtained for Munsell® tiles and child self‐reports of skin color, providing some evidence for the validity of self‐report among New Zealand primary school children, although the lighter colored ITA defined groups were most numerous in this study sample. Statistically significant differences in ITA scores were found by ethnicity, self‐reported skin color, and geographic residence (P < 0.001). Certain Munsell® color tiles were frequently selected as providing a best match to skin color. Conclusion Assessment using Munsell® color charts was simple, inexpensive, and practical for field use and acceptable to children. The results suggest that this method may prove useful for making comparisons with other studies using visual tools to assess skin color. Alignment between the ITA distribution derived from the Munsell® assessment and child skin color self‐reports could probably be improved, particularly with the addition of another ‘light’/’white’ color category in the self‐report instrument.